Peran Dukungan Keluarga Pada Kepuasan Hidup Di Kelompok Lansia Sehat Diwilayah Kerja Puskesmas Mantup Lamongan - Roby Aji Permana (2018)
The aging process in the journey of human life is a natural thing that will be experienced by all people who are blessed with longevity, this process occurs continuously and naturally sustainable. Life satisfaction in the elderly will arise and be experienced if the needs and desires of individuals at a certain time fulfilled and satisfied. This can be done by providing family support because family support has an important role in overcoming the psychological tension in dealing with daily life problems. Aims: This study aims to determine the relationship between family support and life satisfaction elderly. Method The study used an observational quantitative design using cross sectional approach. Sampling technique using purposive sampling. Results The results showed that of 33 respondents, most respondents (53.3%) always received family support, and most respondents got high life satisfaction (76.7%). The statistical test using Chi Square Test (p = 0.05) obtained the result of 0.001 with the value of contingency coefficient of 0.569 indicates the strong relationship correlation. Conclusion There is a very strong relationship between family support and life satisfaction of the elderly. The existence of support from a good family can increase the life satisfaction of the elderly. For health workers to be able to provide counseling to families so that families provide good family support to the elderly.